Digital Storytelling in Higher Education: Highliting the Making Process - Tenia Ramalia (Departement of Mathematics Education, 2023)
Digital storytelling is an innovative and engaging method of learning that has been widely used in various higher education institutions. This research uses a qualitative descriptive analysis method and interviews several students who have created digital storytelling. In this journal, we highlight the importance of digital storytelling as an effective learning tool in higher education and identify the challenges in the process of creating digital storytelling. We also discuss the benefits of using digital storytelling, best practices in its use, and implications and recommendations for educators and higher education institutions. Previous research has shown that digital storytelling is effective in improving students' skills and prosocial behavior in early childhood. Therefore, digital storytelling can be an alternative and effective learning method in higher education